Small scale structures in coupled scalar field dark matter - Beyer, Joschka; Wetterich, Christof (Physics letters, 2014)
We investigate structure formation for ultra-light scalar ﬁeld dark matter coupled to quintessence, in particular the cosmon-bolon system. The linear power spectrum is computed by a numerical solution of the coupled ﬁeld equations. We infer the substructure abundance within a Milky Way-like halo. Estimates of dark halo abundances from recent galaxy surveys imply a lower bound on the bolon mass of about 9 × 10−22 eV. This seems to exclude a possible detection of scalar ﬁeld dark matter through time variation in pulsar timing signals in the near future.
Gesehen am 11.08.2020